2012
DOI: 10.1016/s0140-6736(11)61625-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between different polychemotherapy regimens for early breast cancer: meta-analyses of long-term outcome among 100 000 women in 123 randomised trials

Abstract: SummaryBackgroundModerate differences in efficacy between adjuvant chemotherapy regimens for breast cancer are plausible, and could affect treatment choices. We sought any such differences.MethodsWe undertook individual-patient-data meta-analyses of the randomised trials comparing: any taxane-plus-anthracycline-based regimen versus the same, or more, non-taxane chemotherapy (n=44 000); one anthracycline-based regimen versus another (n=7000) or versus cyclophosphamide, methotrexate, and fluorouracil (CMF; n=18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
732
2
10

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,720 publications
(801 citation statements)
references
References 40 publications
19
732
2
10
Order By: Relevance
“…It is evident that the magnitude of chemotherapy benefit depends on the level of risk of the individual patient [1]. In order to avoid both over- and undertreatment, it is advisable to select the appropriate treatment strategy on the basis of a careful risk assessment for each individual patient.…”
Section: When To Use Chemotherapy In Early Breast Cancer?mentioning
confidence: 99%
See 2 more Smart Citations
“…It is evident that the magnitude of chemotherapy benefit depends on the level of risk of the individual patient [1]. In order to avoid both over- and undertreatment, it is advisable to select the appropriate treatment strategy on the basis of a careful risk assessment for each individual patient.…”
Section: When To Use Chemotherapy In Early Breast Cancer?mentioning
confidence: 99%
“…The advantage of anthracycline-containing 3-drug combinations over CMF was unequivocally confirmed in an individual-patient data meta-analysis of the Early Breast Cancer Trialists' Collaborative Group (EBCTCG) [1]. Altogether, 100,000 patients in 123 randomized trials were included.…”
Section: Which Chemotherapy To Use In Early Breast Cancer?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many older women receive adjuvant endocrine therapy due to the high proportion of hormone receptor positivity (80% to 85%) [4], more favourable toxicity profile, and limited evidence supporting chemotherapy use in women age 70 and over due to their underrepresentation in clinical studies [13]. With the increasing prevalence of breast cancer combined with 5-year survival rates of close to 90% [2], primary care physicians and geriatricians are increasingly relied upon to see and manage patients receiving these therapies [14].…”
Section: Introductionmentioning
confidence: 99%
“…The increased number of breast cancer patients in Japan has forced a rapid adoption of treatment guidelines and consensus approaches, such as the National Comprehensive Cancer Network (NCCN) guidelines and the St. Gallen consensus. The Early Breast Cancer Trialists' Collaborative Group meta-analysis also revealed that anthracyclines reduce the incidences of recurrence and death in modern adjuvant chemotherapy, as do taxanes, particularly for node-positive patients [4]. Recent patients with recurrent breast cancer tend to have already been treated with anthracyclines and taxanes in an adjuvant setting, and will be treated with capecitabine as one of the first-line agents in a metastatic treatment.…”
Section: Introductionmentioning
confidence: 99%